MARCO POLO’S UNSUCCESSFUL ATTEMPTS TO SPREAD CHRISTIANITY IN THE YUAN DYNASTY - Bai, Xuanyu (PEOPLE: International Journal of Social Sciences, 2021)
Since the start of his journey in 1275, Marco Polo has been one of the most significant figures to promote cultural exchange between the East and the West throughout history. Instead of discussing the authenticity of Marco Polo’s experiences in China, this essay focuses on finding the reasons that contributed to Marco Polo’s unsuccessful attempts to spread Christianity in China during the Yuan Dynasty by concentrating on “The Travels of Marco Polo” that he wrote. Combining details from this primary source text along with contemporary documents, artwork, and Chinese culture during the Yuan Dynasty, there were many factors that prevented Christianity from spreading. In particular, this essay explores three key factors: the prevalence of Buddhism, the customs of the Chinese people,and the failure in converting emperor Khan to Christianity during the Yuan Dynasty. In conclusion, the convergence of these factors serves as the explanation for the unsuccessful popularization of Christianity during the Yuan Dynasty.